HEALTH ISSUES AMONG INDIAN WOMEN’S AND GIRLS: A REVIEW - Awasthi, Radhika (IJRDO-Journal of Applied Science, 2015)
Nutrition plays a significant role in promoting women’s health and fitness. Women’s health isa great issue in developing countries because of numerous hindrances, obstacles andimpediments, which force women to ignore their health. Many factors account for thestaggering statistics of ill health among women in the developing nations like India but thefailure of health systems in the majority of the countries to provide accessible care of adequatequality is a major factor. Unintended pregnancy, Mental health, aging, HIV/AIDs, Noncommunicable diseases, reproductive health etc. are responsible for this.Various governmentprogrammes and policies have been framed and some are in the pipeline but the orthodox andobsolete mentality of the people is still a big hurdle and this is the cause that comes in the pathof women’ health. This article focuses on the major health issues affecting women’s health.